2020
DOI: 10.1108/tr-05-2019-0155
|View full text |Cite
|
Sign up to set email alerts
|

Educational tourism and experiential learning: students’ perceptions of field trips

Abstract: Purpose This paper aims to investigate participants’ motivations and perceptions of a field trip. Specifically, this paper examines if and how students’ perceptions change with time and it explores the main factors for ensuring success in an experiential learning tourism program. Design/methodology/approach The study gathered and compared data collected in two points in time – immediately at the end of the experience and two months afterward. T-tests for paired samples were used to examine potential differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…The results of the analysis highlight four key findings: 1) the call for an active communal engagement, participation, and collaboration in developing the village for EET, 2) the need for an effective digital marketing strategy, 3) EET management should be communal instead of commercial entities, and 4) the need for public and entertaining facilities. EET is perceived as a socio-educational entity that requires social inclusion (Chandralal, 2010), social and professional networking (Arcodia et al, 2020), cultural sensitivity (Lo et al, 2014;Syarifuddin, S., Abduh, A., & Talib, A., 2017), and in-person learning (Anas et al, 2020). Grounded in social inclusion theory (Gidley et al, 2010), the role of community participation in developing environmentally-based education is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the analysis highlight four key findings: 1) the call for an active communal engagement, participation, and collaboration in developing the village for EET, 2) the need for an effective digital marketing strategy, 3) EET management should be communal instead of commercial entities, and 4) the need for public and entertaining facilities. EET is perceived as a socio-educational entity that requires social inclusion (Chandralal, 2010), social and professional networking (Arcodia et al, 2020), cultural sensitivity (Lo et al, 2014;Syarifuddin, S., Abduh, A., & Talib, A., 2017), and in-person learning (Anas et al, 2020). Grounded in social inclusion theory (Gidley et al, 2010), the role of community participation in developing environmentally-based education is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Job prospects, housing prices, the city's identity, the aesthetics and infrastructure of the town, and the citizens' enhanced satisfaction in their community. It is then echoed by Arcodia et al (2020) that creating a better education tourism needs to build social and professional networks and innovative educational methods. In Indonesia, Ekasani et al (2020) found that Kampung Inggris has created an ecology of English immersion education, where English teachers, learners, English courses, expatriates, travel bureaus, hotels, local small businesses, and culinary are bound educationally, socially, and economically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers like Arcodia et al (2014) have developed a relevant trajectory on experiential learning using academic trips. Th rough these investigations, the contribution of the studies to motivations and perceptions of experience has been proven, as well as the identifi cation of three important factors for meeting expectations: social and professional connections, learning, and traditional yet engaging teaching (Arcodia et al, 2020). However, these authors recognize the need to develop more studies that expose practical fi ndings within the contexts of tourism, hospitality, and event management (Arcodia & Dickson, 2009, 2013.…”
Section: Theoretical Background Of the Researchmentioning
confidence: 99%
“…It is also worth noticing that in this way, tourism can also be thought of as a form of learning, allowing people to learn something new through their experiences, a model called Experiential Learning. Turning a tourist visit into an educational opportunity using a chatbot can be a new form of Experiential Tourism (Ruhanen, 2005 ; Arcodia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%